A systematic review of motivational and attentional variables on children's fundamental movement skill development: the OPTIMAL theory. Issue 1 (1st January 2021) - Simpson, Thomas; Ellison, P.; Carnegie, E.; Marchant, D.
ABSTRACT: An external focus of attention, enhanced expectancies and autonomy support are key independent and interactive characteristics which enhance motor learning. These OPTIMAL (Optimizing Performance Through Intrinsic Motivation and Attention for Learning) characteristics have proven supportive of adult's motor learning yet, their effect on children's motor learning is comparatively under-explored. Fifty-five studies were systematically reviewed to outline the impact of OPTIMAL variables on children's motor learning, specifically foundational movement skills (FMS). Thirty-five studies examined an external focus of attention, whereas relatively few addressed enhanced expectancies ( n  = 12) and autonomy support ( n  = 8). Only 2 explored the interaction between OPTIMAL variables. Results show emerging evidence that OPTIMAL variables contribute to children's effective motor learning. Despite this initial support, there is a paucity of research regarding the impact of OPTIMAL variables across the full FMS range (i.e. a skewness towards object manipulation skills). Moreover, children's different developmental characteristics may moderate the beneficial effects of OPTIMAL variables. Additionally, the attentional and motivational mechanisms underpinning OPTIMAL learning (e.g. self-efficacy) in children requires future work. Finally, there is a need for future combinatory research addressing OPTIMAL variables in children (e.g. enhanced expectancies with autonomy support). The theoretical and practical implications of the findings are discussed throughout.